2019
DOI: 10.4103/njs.njs_36_18
|View full text |Cite
|
Sign up to set email alerts
|

Submental dermoid cyst mimicking double chin

Abstract: Dermoid cysts are developmental cysts, arising from entrapped midline ectodermal tissue lined by epidermis, with skin appendages present in the fibrous wall when the 1st and 2nd branchial arches of each side fuse and the entrapped tissues then undergo proliferation and cystic transformation. A 27-year-old male reported with a single large swelling in the submental region of 1-year duration, which was diagnosed as dermoid cyst after surgical excision using extraoral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The patient in our case was a 57-year-old having complaints regarding swallowing and speech and with the swelling present centrally. It implies that the swelling in our patient was a long-standing one, different from the one presented by Wadhera et al A similar case was noted by Bommaji et al in 2019 where a 27-year-old male patient reported swelling in the submental region [ 11 ]. The patient had a history of impact five years earlier after which the swelling was noted.…”
Section: Discussionmentioning
confidence: 47%
“…The patient in our case was a 57-year-old having complaints regarding swallowing and speech and with the swelling present centrally. It implies that the swelling in our patient was a long-standing one, different from the one presented by Wadhera et al A similar case was noted by Bommaji et al in 2019 where a 27-year-old male patient reported swelling in the submental region [ 11 ]. The patient had a history of impact five years earlier after which the swelling was noted.…”
Section: Discussionmentioning
confidence: 47%
“…However, these cysts usually presented with thin walls. The existence of cutaneous adnexa is considered the main histological difference with epidermoid cysts [13][14][15][16] . This finding was consistent with the current study observations.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Surgical enucleation is the treatment of choice for sublingual and submandibular/submental benign cystic lesions. It was recommended in the pieces of literature that, the lesions above the mylohyoid muscle with dimensions less than 6 cm in diameter were approached intraorally and lesions below the mylohyoid muscles with dimensions more than 6 cm in diameter were removed by extraoral approach [16,17] . Furthermore, marsupialization had also been documented as an alternative treatment in cases of large cysts [18] .…”
Section: Conflict Of Interestmentioning
confidence: 99%